SKRINING RHIZOBAKTERIA PENGHASIL INDOLE ANCETID ACID PENGINDUKSI PERTUMBUHAN DARI RHIZOSFIR CABAI (Capsicum annuum L.) - Jumsu Trisno (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2011)
Rhizobacteria was a colonialist bacterial at rooting area that had capacity to produce IAA and enhance plant growth. Rhizobacteria indigenus chili had ability to produce IAA and induces various of plant growth. IAA production was not always linked with the ability to enhance plant growth. Obtained there were 11 isolates with various of morphological characters and had ability as RMSD (Plant Growt Promoting Rhizobacteria) with an effective increase in growth from 57.88 to 82.80%.Key words: Rhizobacteria, IAA, Growth, Chili Rhizosfer